Involving female Omani English language teachers in evaluating curriculum materials - Al-Senaidi, Fatma Salim; Wyatt, Mark (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
English language teachers have an important role in evaluating curriculum materials used with their learners. Accordingly, feedback elicited from teachers should be collected, collated and referred to by curriculum planners initiating educational reform. There are very few accounts, though, of such processes and it is sometimes feared that teachers’ voices (including those of non-native speaker females in Middle Eastern societies) are unheard. Drawing on both quantitative and qualitative data, this article focuses on female primary school English teachers’ perceptions of their own involvement in evaluating materials in the Sultanate of Oman. It reveals that, although the teachers demonstrate awareness of materials evaluation processes, their experience of being involved in them is limited. It considers how this involvement could be increased.